Anti-semitism and its metaphysical origins - Patterson, David, 1948- (New York, NY : Cambridge University Press, 2015)
"This book articulates a deeper understanding of the phenomenon of Jew hatred as a metaphysical aspect of the human soul. Proceeding from the Jewish thinking that the anti-Semites oppose, David Patterson argues that anti-Semitism arises from the most ancient of temptations, the temptation to be as God, and thus to flee from an absolute accountability to and for the other human being"--
Introduction: anti-Semitism as deicide -- 1. Preliminary explanations -- 2. The arrogation of God: Christian theological anti-Semitism -- 3. Islamic jihadism: religious-fanatic anti-Semitism -- 4. The elimination of God: philosophical anti-Semitism in modern thought -- 5. National socialist anti-Semitism -- 6. Antihistorical anti-Semitism: Holocaust denial -- 7. Anti-Zionist anti-Semitism -- 8. Jewish Jew hatred -- 9. Sounding the depths of the anti-Semitic soul: Arthur Miller's Focus -- Concluding reflection: the messianic side of the soul of Adam.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Antisemitism; Antisemitism -- History; Antisémitisme.; Antisémitisme -- Histoire; antisemitism; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Antisemitism; Antisemitismus; Metaphysik; Philosophische Anthropologie; History